The factors that influence the effectiveness anti-corruption initiatives / NurAzila Ahmad Ramli and Fatin Afiqah Muhd Lotfi - Ahmad Ramli, NurAzila; Muhd Lotfi, Fatin Afiqah (2018)
This chapter focuses on the background of the study, which is factors that influence the effectiveness of anti-corruption initiatives. The presentation of this chapter begins with the research background, followed by the problem statement, research questions, research objectives, scope of the study, significant of the study and lastly the definition of terms and concepts used in this study.